Perceptions of stress and coping strategies among international women of color college students in the United States - Sanyaolu, Olutosin A; Nabors, Laura; Reeves-Doyle, Brandy; King, Keith; Adabla, Samuel (Journal of International Students, 2026)
International women of color in U.S. higher education institutions may experience unique stressors, which can affect their mental health and academic performance. This research examined perceptions of stressors influencing health and the coping strategies employed by international women of color in college to inform tailored approaches that better support their well-being and academic achievement. In-depth interviews were conducted with 20 international women of color at a large public Midwestern university. Data were analyzed using inductive thematic analysis to identify emergent themes. Participants described stressors, including uncertainty about the future, financial strain, academic pressures, immigration constraints, and sociocultural challenges. These stressors were reported to interfere with their well-being, increasing anxiety and impacting academic engagement. Coping strategies included social support, self-care activities, and structured planning, with participants preferring informal coping mechanisms. The findings reveal distinct support needs and opportunities to enhance culturally responsive systems for student well-being and success.